Coach mid-season replacement and team performance in professional soccer - Lago-Penas, C. (Journal of Human Kinetics, 2011)
The coaching carousel or turnover is an extreme but frequently occurring phenomenon in soccer. Among the reasons for firing a coach, the most common is the existence of a shock-effect: a new coach would be able to motivate the players better and therefore to improve results. Using data from the Spanish Soccer League during the seasons from 1997-1998 to 2006-2007, this paper investigates the relationship between team performance and coach change over time. The empirical analysis shows that the shock effect of a turnover has a positive impact on team performance in the short term. Results reveal no impact of coach turnover in the long term. The favourable short-term impact on team performance of a coach turnover is followed by continued gradual worsening of results. The turnover effect is nonexistent when the comparison between the new coach and the old coach is done over 10, 15 or 20 matches before and after termination.